Pengaruh Strategi Daftar-Grup-Label tentang Interpretasi Membaca Siswa Pemahaman - Afore Tahir Harefa (Neolectura, 2021)
Reading at the level of interpretive understanding is a student activity to respond, get information and meaning by making inferences and reading between the lines of the reading text. This study reveals the problems, namely: students are not able to identify content words such as verbs, nouns, adjectives, and adverbs from the text, students lack vocabulary, students are not able to answer comprehension questions from the text by applying the List-Group-Label Strategy in the teaching and learning process. reading narrative text. The purpose of this study was to determine whether or not there was a significant effect of List-Group-Label Strategy on Students' Reading Comprehension in Narrative Text. This research is a quasi-experimental design. The population in this study were junior high school students and the sample was class VIII students which consisted of two classes as the experimental class and the control class. Each class consists of 30 students. Researchers selected samples using saturated sampling technique. The instrument used in data collection is a written test. Next, the researcher gave a pretest and posttest to the experimental group and the control group to determine the normality of the data and the homogeneity of the sample. After conducting the research, the researcher analyzed the data and produced hypothesis testing, the t-count was 5.067 and the t-table was 2.002. While t-count (5.067) > t-table (2.002), it can be concluded that Ho is rejected and Ha is accepted. In conclusion, there is a significant effect of the List-Group-Label Strategy on students' reading comprehension in narrative texts